Multi-party business process compliance monitoring through IoT-enabled artifacts. (March 2018) - Meroni, Giovanni; Baresi, Luciano; Montali, Marco; Plebani, Pierluigi
Highlights: A novel approach to monitor multi-party business processes is proposed. Monitoring is distributed among the physical artifacts interacting with the process. The approach relies on E-GSM to continuously validate the execution of the process. To easily adopt the approach, transformation rules from BPMN to E-GSM are presented. A prototype implementation of the approach is also presented. Abstract: Monitoring the compliance of the execution of multi-party business processes is a complex and challenging task: each actor only has the visibility of the portion of the process under its direct control, and the physical objects that belong to a party are often manipulated by other parties. Because of that, there is no guarantee that the process will be executed — and the objects be manipulated — as previously agreed by the parties. The problem is usually addressed through a centralized monitoring entity that collects information, sent by the involved parties, on when activities are executed and the artifacts are altered. This paper aims to tackle the problem in a different and innovative way: it proposes a decentralized solution based on the switch from control- to artifact-based monitoring, where the physical objects can monitor their own conditions and the activities in which they participate. To do so, the Internet of Things (IoT) paradigm is exploited by equipping physical objects with sensing hardware and software, turning them into smart objects. To instruct these smart objects, an approach to translate classical Business Process Model and Notation (BPMN) process models into a set of artifact-centric process models, rendered in Extended-GSM (E-GSM) (our extension of the Guard-Stage-Milestone (GSM) notation), is proposed. The paper presents the approach, based on model-based transformation, demonstrates its soundness and correctness, and introduces a prototype monitoring platform to assess and experiment the proposed solution. A simple case study in the domain of advanced logistics is used throughout the paper to exemplify the different parts of the proposal.